PENGARUH PENGGUNAAN MEDIA TIMELINE TERHADAP KEMAMPUAN MAHASISWA DALAM MEMAHAMI MATERI PERADABAN ISLAM - Edo Alvizar Dayusman; Sibawaihi Sibawaihi; Nurhadi nurhadi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Historical material is one of the most important materials to be conveyed to students. Islamic civilization is one of the materials taught at the lecture level, especially at Islamic Religious Universities. In the learning process, often Islamic civilization material is not conveyed well to students because it uses lecture methods and powerpoint media only. In dealing with this problem, the use of timeline media by presenting a coherent and concrete timeline of events becomes a solution to convey Islamic civilization material. The purpose of this study is to determine the influence of the use of timeline media on the ability to understand Islamic civilization material. This study uses a type of quantitative research pseudo-experiment with Nonequivalent control group design. The population used in this study was all 2nd semester students of the Department of Arabic Language Education class A UIN Sunan Kalijaga which totaled 29 people. The sample used was the entire population of 29 people. Data collection technique using coesiner instrument with Likert scale model. The analysis technique used in this study is a simple linear regression analysis technique. The results obtained were a significant influence between the use of timeline media on students' ability to understand Islamic Civilization material by 47.6%.